The use of screening, identification, assessment and support policy to support vulnerable learners - Inneth Baby Makofane; Simon Mfula Ndlovu; Hunadi Mphahlele; Mahlapahlapana Johannes Themane (International Journal of Educational Management and Development Studies)
South African schools are becoming overwhelmed by the large numbers of learners who experience various vulnerabilities, including socio-economic issues and psychosocial factors. The policy for Screening, Identification, Assessment, and Support (SIAS) serves as a guiding tool to teachers, in providing necessary support to vulnerable learners. This study sought to explore the teachers' views on the implementation of the SIAS policy to support vulnerable learners. The qualitative research approach was employed. The study is interpretive and selected the case study research design. Purposive sampling was employed to sample five secondary schools for participation. Within the five sampled schools, ten teachers, five school-based support team members, and five principals were selected for participation. The sampling criteria was based on participants’ experiences in implementing the SIAS policy. Data was collected through semi-structured interviews and document review. The data were analysed thematically. The study revealed misconception of the SIAS policy, the incredibility of school-based support teams, inappropriate learner profiling, lack of comprehensive psychosocial support systems, poor parental involvement, the teachers’ preparedness in contributing towards enabling schooling environments. It is recommended that the Department of Basic Education develop comprehensive policy guidelines to address psychosocial support to vulnerable learners in rural schools, provide sufficient resources to enhance the support measures and devise strategies to continuously assess the efficacy of the support systems. Lastly, the Department of Education should make it a priority to actively engage parents or guardians in the learners’ academic activities.